The Psychological Impact of the COVID-19 Pandemic on Brief Psychological Services Clients - Roxas, Gilana Kim T (Archīum Ateneo, 2021)
The COVID-19 pandemic has brought about not only the risk of death from the virus, but also rising rates of psychological distress. In response, the Brief Psychological Services Program (BPS) was organized to provide Filipinos free remote access to psychological support. This study thus aims to: (1) evaluate the characteristics of individuals who sign up for BPS; (2) describe their levels of psychological distress; and (3) describe the preliminary responses to the intervention. From January 10, 2021 to May 4, 2021, a total of 1,685 respondents signed up and consented to research participation. Majority were females aged 18-33 who had not previously sought mental health services. The primary reasons for referral were excessive worrying, feeling overwhelmed, and persistent low mood/low energy. On the COVID-19 Impact Scale, majority reported moderate-to-severe change in routines and experiences of stress related to COVID. From February 17, 2021 to July 22, 2021, a total of 309 participants answered the pre-session measures. Results from the DASS-21 showed that 50.1% reported moderate-to-severe stress; 51.1% reported extremely severe anxiety; and 41.1% reported extremely severe depression. The results of the Brief COPE showed that the most frequently used coping methods were self-blame and self-distraction, while the less frequently used were substance use, denial, humor, and religion. Finally, majority of participants reported being feeling “somewhat better” about their problem after the session.